A new Dicranophragma (Diptera: Limoniidae) from a hypogeous environment in Catalonia (Iberian Peninsula) - Mederos, Jorge; Gago, Sergi; Brañas, Neus; Fadrique, Floren; Caballero-López, Berta; Masó, Glòria (European Journal of Taxonomy, 2020)
A new species of Limnophilinae (Diptera: Limoniidae), Dicranophragma (Brachylimnophila) relictum Mederos sp. nov., is described. This is the third species of this genus recorded from the Iberian Peninsula. This new species was discovered in a cave in the Sant Llorenç del Munt i Serra de l’Obac Natural Park, Barcelona Province (Catalonia) and it is the first record of a species of this genus from a hypogeous environment. The absence of suitable ecological conditions for the survival of this new species, particularly in the vicinity of the cave, suggests that this population of D. relictum Mederos sp. nov. is isolated. Dicranophragma relictum Mederos sp. nov. is characterized by the following features: a general grey-to-greenish-grey coloration on its thorax and a dark-grey abdomen; wings more than four times longer than wide; pale-brown-to-yellowish tinted wings, with brown veins and a well-marked stigma; in the male genitalia the upper part of the aedeagus is acute when viewed laterally and is longer than the lower part. A key is provided for separating the three species of Dicranophragma known to be present in the Iberian Peninsula.